INTERNALISASI NILAI-NILAI KARAKTER MELALUI PENDEKATAN BUDAYA KEAGAMAAN DALAM MENCEGAH PERILAKU BULLYING PESERTA DIDIK DI MADRASAH IBTIDAIYAH KAB. PARIGI MOUTONG - Wahyuningsih Riyadi, Nur Eka; Mardi Lestari (Pusat Studi Gender dan Anak, IAIN Palu, 2023)
Abstract The aim of this research is to determine the forms of internalization of character values ​​through a religious culture approach in preventing bullying behavior among students at Madrasah Ibtidaiyah Parigi Moutong Regency as well as the impact of internalizing character values ​​through a religious culture approach in preventing bullying behavior among students in Madrasah Ibtidaiyah Parigi Moutong Regency. The type of research used in this research is descriptive qualitative. The subjects of this research are teachers and students. Data collection used observation, interview and documentation techniques which were analyzed using data reduction, data presentation and data verification methods. Forms of internalizing Character values ​​towards Bullying Behavior among Students at Madrasah Ibtidaiyah Parigi Moutong Regency firstly, instilling religious character values ​​through extra-curricular activities, through getting used to good behavior and through advice, secondly instilling the character values ​​of tolerance, instilling character values Social care. The impact of internalizing character values ​​on bullying behavior among students at Madrasah Ibtidaiyah, Parigi Moutong Regency has a positive impact. This can be seen from changes in behavior for the better among students as well as reducing and preventing bullying behavior in the school.